Cultural adaptation and validation of the caring behaviors assessment tool into Spanish - Juan M. Leyva-Moral; Carolina Watson; Nina Granel; Cecilia Raij-Johansen; Ricardo A. Ayala (BMC, 2024)
Abstract Background The aim of the research was to translate, culturally adapt and validate the Caring Behaviors Assessment (CBA) tool in Spain, ensuring its appropriateness in the Spanish cultural context. Methods Three-phase cross-cultural adaptation and validation study. Phase 1 involved the transculturation process, which included translation of the CBA tool from English to Spanish, back-translation, and refinement of the translated tool based on pilot testing and linguistic and cultural adjustments. Phase 2 involved training research assistants to ensure standardized administration of the instrument. Phase 3 involved administering the transculturally-adapted tool to a non-probabilistic sample of 402 adults who had been hospitalized within the previous 6 months. Statistical analyses were conducted to assess the consistency of the item-scale, demographic differences, validity of the tool, and the importance of various caring behaviors within the Spanish cultural context. R statistical software version 4.3.3 and psych package version 2.4.1 were used for statistical analyses. Results The overall internal consistency of the CBA tool was high, indicating its reliability for assessing caring behaviors. The subscales within the instrument also demonstrated high internal consistency. Descriptive analysis revealed that Spanish participants prioritized technical and cognitive aspects of care over emotional and existential dimensions. Conclusions The new version of the tool proved to be valid, reliable and culturally situated, which will facilitate the provision of objective and reliable data on patients beliefs about what is essential in terms of care behaviors in Spain.